Sustainable steel through hydrogen plasma reduction of iron ore: Process, kinetics, microstructure, chemistry. (July 2021) - Souza Filho, I. R.; Ma, Y.; Kulse, M.; Ponge, D.; Gault, B.; Springer, H.; Raabe, D.
Abstract: Iron- and steelmaking is the largest single industrial CO2 emitter, accounting for 6.5% of all CO2 emissions on the planet. This fact challenges the current technologies to achieve carbon-lean steel production and to align with the requirement of a drastic reduction of 80% in all CO2 emissions by around 2050. Thus, alternative reduction technologies have to be implemented for extracting iron from its ores. The hydrogen-based direct reduction has been explored as a sustainable route to mitigate CO2 emissions, where the reduction kinetics of the intermediate oxide product Fex O (wüstite) into iron is the rate-limiting step of the process. The total reaction has an endothermic net energy balance. Reduction based on a hydrogen plasma may offer an attractive alternative. Here, we present a study about the reduction of hematite using hydrogen plasma. The evolution of both, chemical composition and phase transformations was investigated in several intermediate states. We found that hematite reduction kinetics depends on the balance between the initial input mass and the arc power. For an optimized input mass-arc power ratio, complete reduction was obtained within 15 min of exposure to the hydrogen plasma. In such a process, the wüstite reduction is also the rate-limiting step towards complete reduction. Nonetheless, the reduction reaction is exothermic, and its rates are comparable with those found in hydrogen-based direct reduction. Micro- and nanoscale chemical and microstructure analysis revealed that the gangue elements partition to the remaining oxide regions, probed by energy dispersive spectroscopy (EDS) and atom probe tomography (APT). Si-enrichment was observed in the interdendritic fayalite domains, at the wüstite/iron hetero-interfaces and in the oxide particles inside iron. With proceeding reduction, however, such elements are gradually removed from the samples so that the final iron product is nearly free of gangue-related impurities. Our findings provide microstructural and atomic-scale insights into the composition and phase transformations occurring during iron ore reduction by hydrogen plasma, propelling better understanding of the underlying thermodynamics and kinetic barriers of this essential process. Graphical abstract: Image, graphical abstract